Electrocardiographic and clinical predictors of torsades de pointes induced by almokalant infusion in patients with chronic atrial fibrillation or flutter: a prospective study - Houltz, Birgitta; Darpö, Börje; Edvardsson, Nils; Blomström, Per; Brachmann, Johannes; Crijns, Harry J.g.m.; Jensen, Steen M.; Svernhage, Elisabeth; Vallin, Hans; Swedberg, Karl (Pacing and clinical electrophysiology, 1998)
The aim of this study was to identify predictors of torsades de pointes (TdP) in patients with atrial fibrillation (AF) or flutter exposed to the Class III antiarrhythmic drug almokalant. TdP can be caused by drugs that prolong myocardial repolarization. One hundred patients received almokalant infusion during AF (infusion 1) and 62 of the patients during sinus rhythm (SR) on the following day (infusion 2). Thirty-two patients converted to SR. Six patients developed TdP. During AF, T wave alternans was more common prior to infusion (baseline) in patients developing TdP (50% vs 4%, P < 0.01). After 30 minutes of infusion 1, the TdP patients exhibited a longer QT interval (493 ± 114 vs 443 ± 54 ms [mean ± SD], P < 0.01), a larger precordial QT dispersion (50 ± 74 vs 27 ± 26 ms, P < 0.05), and a lower T wave amplitude (0.12 ± 0.22 vs 0.24 ± 0.16 mV. P < 0.01). After 30 minutes of infusion 2, they exhibited a longer QT interval (672 ± 26 vs 489 ± 74 ms, P < 0.001), a larger QT dispersion in precordial (82 ± 7 vs 54 ± 52 ms, P < 0.01) and extremity leads (163 ± 0 vs 40 ± 34 ms, P < 0.001), and T wave alternans was more common (100% vs 0%, P < 0.001). Risk factors for development of TdP were at baseline: female gender, ventricular extrasystoles, and treatment with diuretics; and, after 30 minutes of infusion: sequential bilateral bundle branch block, ventricular extrasystoles in bigeminy, and a biphasic T wave. Patients developing TdP exhibited early during almokalant infusion a pronounced QT prolongation, increased QT dispersion, and marked morphological T wave changes.